Working poor? An analysis of low wage employment in Italy - Claudio Lucifora (Fondazione Eni Enrico Mattei (FEEM), 1997)
In this paper we look at the evolution of low wage employment in Italy using different data sets, at the individual level, for the 1975-1993 period. The structure of the paper is as follows: first, the nature and the extent of low pay in Italy is analysed in terms of the existing pay setting institutions. Second, both a descriptive analysis of the main features of low pay employment, as well as the working experience of individuals over the life-cycle are offered. The main determinants of low wages are estimated and the - ceteris paribus - probability of being low paid is given for different stylised "individuals". Third, we explore whether low pay is a transitory or a permanent feature of the individual wage profile. Mobility patterns over deciles of the wage distribution are analysed and a number of summary indicators are offered.
Keywords: J3; J6; I3; 330; Wages; Mobility; Low pay employment